Implementación del Software SimSched DBS para un yacimiento polimetálico modificando variables geométricas (2018)
The following article intends to study the final pit of a hypothetical polymetallic deposit using the SimSched DBS software, based on a set of consecutive stages such as final pit with nested pits, phase design, operational sequence period by period, among others; this is done through the modification and analysis of geometric variables such as the slope angle, the vertical advance and the bottom of the pit. In addition, the close relationship between the variation of the Net Present Value (NPV) and the modification of the three geometric variables considered above is studied.